The Breathalyzer and its Applications - Borkenstein, R. F.; Smith, H. W. (Medicine, Science and the Law, 1961)
The Breathalyzer was designed and developed by R. F. Borkenstein in 1954 for the analysis of alcohol in samples of breath. In this article the authors describe this equipment, its method of operation and accuracy. The factors relating this measurement to the concentration of alcohol in the blood are discussed in detail as are its specificity for alcohol and its application in law enforcement.